Characterisation of the Dynamic Interactions between Complex N‐Glycans and Human CD22. (17th October 2019) - Di Carluccio, Cristina; Crisman, Enrique; Manabe, Yoshiyuki; Forgione, Rosa Ester; Lacetera, Alessandra; Amato, Jussara; Pagano, Bruno; Randazzo, Antonio; Zampella, Angela; Lanzetta, Rosa; Fukase, Koichi; Molinaro, Antonio; et al.
Abstract: CD22 (Siglec‐2) is a B‐cell surface inhibitory protein capable of selectively recognising sialylated glycans, thus dampening autoimmune responses against self‐antigens. Here we have characterised the dynamic recognition of complex‐type N ‐glycans by human CD22 by means of orthogonal approaches including NMR spectroscopy, computational methods and biophysical assays. We provide new molecular insights into the binding mode of sialoglycans in complex with h‐CD22, highlighting the role of the sialic acid galactose moieties in the recognition process, elucidating the conformational behaviour of complex‐type N ‐glycans bound to Siglec‐2 and dissecting the formation of CD22 homo‐oligomers on the B‐cell surface. Our results could enable the development of additional therapeutics capable of modulating the activity of h‐CD22 in autoimmune diseases and malignancies derived from B‐cells. Abstract : Molecular clues about dynamic recognition of complex‐type N ‐glycans by human CD22. We highlight the importance of the sialic acid galactose moieties in the recognition process and study the conformational behaviour of complex biantennary glycans in depth throughout their binding to h‐CD22. We also analyse the molecular basis of CD22 homo‐oligomer formation on B‐cell surfaces.